2017
DOI: 10.2147/ott.s133504
|View full text |Cite
|
Sign up to set email alerts
|

Novel role of granulocyte-macrophage colony-stimulating factor: antitumor effects through inhibition of epithelial-to-mesenchymal transition in esophageal cancer

Abstract: PurposeRecent studies demonstrate the possible antitumor effects of granulocyte-macrophage colony-stimulating factor (GM-CSF); however, the exact mechanism is still unclear. The aim of our study was to analyze the effects of GM-CSF on multiple biological functions of human esophageal cancer (EC) cell lines and to explore the potential mechanism of its antitumor effects.Materials and methodsEca109/9706 human EC cells were examined. Cell proliferation, apoptosis, and migration were analyzed using cell proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…In agreement with the present study, anti-cancer roles of GM-CSF are shown in colon (COLO 205) ( Nebiker et al, 2014 ), prostate (patient tissues) ( Wei et al, 2016 ), CCA (KKU-213A) ( Panya et al, 2018 ), bladder (MGHU3, UMUC3) ( Hori et al, 2019 ), cervical (patient tissues) ( Jiang et al, 2015 ) and esophageal cancers (Eca-109, EC9706) ( Zhang et al, 2017 ), through activations of CD16-positive monocytes and effector T-cells, but suppressions of M2-mediated angiogenesis and pro-inflammatory mediator productions ( e.g. , cyclooxygenase-2 and inducible nitric oxide synthase).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with the present study, anti-cancer roles of GM-CSF are shown in colon (COLO 205) ( Nebiker et al, 2014 ), prostate (patient tissues) ( Wei et al, 2016 ), CCA (KKU-213A) ( Panya et al, 2018 ), bladder (MGHU3, UMUC3) ( Hori et al, 2019 ), cervical (patient tissues) ( Jiang et al, 2015 ) and esophageal cancers (Eca-109, EC9706) ( Zhang et al, 2017 ), through activations of CD16-positive monocytes and effector T-cells, but suppressions of M2-mediated angiogenesis and pro-inflammatory mediator productions ( e.g. , cyclooxygenase-2 and inducible nitric oxide synthase).…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the cancer milieu, the controversial roles of GM-CSF were demonstrated. Cancer-promoting functions are established in breast, glioma, liver, and pancreatic cancers ( Bayne et al, 2012 ; Kohanbash et al, 2013 ; Lin et al, 2017 ; Reggiani et al, 2017 ; Revoltella, Menicagli & Campani, 2012 ), whereas cancer-preventing roles are demonstrated in bladder, cervical, colon, esophageal, and prostate cancers ( Hori et al, 2019 ; Jiang et al, 2015 ; Nebiker et al, 2014 ; Wei et al, 2016 ; Zhang et al, 2017 ). In CCA, there is a report demonstrating that cirrhosis-related iCCA-derived GM-CSF promotes intense neutrophil infiltration ( Sasaki et al, 2003 ); however, the contradictory result is demonstrated in the spontaneous iCCA mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous reports suggesting that CSF2 could inhibit the development of cancer (13)(14)(15)67), we further investigated the serum samples from patients with EC, CRC, GC, LC, and MC. The s-CSF2-Ab levels were significantly higher in patients with EC, CRC, GC, and LC, but not in those with MC, compared with HDs (Figure 5; Table 7).…”
Section: Elevated S-csf2-ab Levels In Patients With Cancermentioning
confidence: 99%